Solid electrolyte material and solid-state lithium battery

By preparing solid electrolyte materials that combine Zr, Y, In with metal Li, and using gradient heating technology, the capacity retention problem of solid-state lithium batteries in high and low temperature environments is solved, and the performance and life of the batteries at different temperatures is significantly improved.

CN119833737AInactive Publication Date: 2025-04-15DONGGUAN WILIYOUNG ELECTRONICS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510126516.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The capacity retention rate of solid-state lithium batteries in high and low temperature environments is still not ideal, especially under extreme temperature conditions, which affects the working efficiency and life of the battery.

Method used

The solid electrolyte material is prepared by mixing ZrCl4, YCl3, InCl3, LiCl and Li2O and then heating, insulation, cooling and ball milling, and the gradient heating method is used to improve the performance of solid lithium batteries at different temperatures.

Benefits of technology

It significantly improves the capacity retention rate of solid-state lithium batteries at room temperature, low temperature and high temperature, ensures that the battery operates stably within a wide temperature range, and extends the battery's cycle life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of solid-state lithium batteries, and particularly relates to a solid electrolyte material and a solid-state lithium battery. The solid electrolyte material is prepared by the following steps: mixing ZrCl4, YCl, InCl, LiCl and Li2O, heating, preserving heat, cooling, and ball-milling. Wherein the molar ratio of the ZrCl4 to the YCl to the InCl to the LiCl to the Li2O is (0.1 to 0.2) to 0.5 to (0.3 to 0.5) to (1.2 to 1.5) to (0.2 to 0.4). The solid-state lithium battery prepared by the invention has excellent capacity retention ratio under the conditions of normal temperature, high temperature and low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a solid electrolyte material and a solid-state lithium battery. Background Art

[0002] Solid-state lithium batteries have a higher energy density than traditional lithium-ion batteries, which means that solid-state lithium batteries can store more electrical energy at the same volume or weight. For speaker toys, this can extend the playback time and allow users to enjoy a longer music experience. The capacity retention rate of a solid-state lithium battery refers to the percentage of the battery that can maintain its initial capacity after multiple charge and discharge cycles. This indicator is very important for evaluating the long-term performance and life of the battery.

[0003] Although solid-state lithium batteries have many potential advantages, such as higher safety, higher energy density and longer cycle life, they still face some technical challenges in practical applications. 1. Interface stability: Poor interface contact between solid electrolyte and electrode material will lead to higher interface resistance, which will affect the charge and discharge efficiency and capacity retention of the battery. The highly active lithium metal negative electrode is prone to form an unstable solid electrolyte interface during the cycle, resulting in capacity decay. 2. Conductivity of solid electrolyte: Although solid electrolytes can theoretically provide higher safety, their ionic conductivity at room temperature is usually lower than that of liquid electrolytes, which limits the fast charging capability and low temperature performance of the battery. 3. Temperature adaptability: At high temperature: Some solid electrolyte materials may undergo chemical decomposition or physical changes under high temperature conditions, affecting the stability and capacity retention of the battery. At low temperature: The ion mobility of solid electrolytes at low temperatures decreases significantly, resulting in an increase in the internal impedance of the battery, affecting the charge and discharge efficiency and capacity retention of the battery. 4. Capacity retention under high and low temperature conditions: The performance of solid-state lithium batteries under extreme temperatures is still a challenge. Under low temperature conditions, the ionic conductivity of solid electrolytes is greatly reduced, which seriously affects the working efficiency and capacity retention of the battery. In high temperature environments, although solid-state batteries are more stable than liquid batteries, if the temperature is too high, it may also trigger other side reactions of the materials, which will also affect the performance and life of the battery.

[0004] To overcome these problems, researchers are currently exploring various methods, including developing new solid electrolyte materials, improving the design of the electrode / electrolyte interface, and optimizing the overall structure of the battery. With the development and improvement of these technologies, solid-state lithium batteries are expected to be more widely used in the future. Audio toys have a wide range of usage environments and may be used in a variety of different environments, from the cold winter in the north to the hot summer in the south. The battery must be able to work stably over a wide temperature range to ensure a consistent user experience. Considering China's geographical and climatic differences, such as the severe cold in the north in winter and the hot summer in the south, the batteries used in audio toys must be able to adapt to these extreme conditions. For example, in the winter in the north, the battery needs to ensure sufficient power output in sub-zero temperatures; while in the summer in the south, the battery needs to work stably at high temperatures without overheating or performance degradation. However, the capacity retention rate of solid-state lithium batteries currently on the market in high and low temperature environments is still not ideal.

[0005] Therefore, there is an urgent need for a solid electrolyte material and a solid-state lithium battery. Summary of the invention

[0006] The purpose of the present invention is to provide a solid electrolyte material and a solid-state lithium battery.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A solid electrolyte material is prepared by mixing ZrCl4, YCl3, InCl3, LiCl and Li2O, heating and then keeping the mixture warm, and then cooling and then ball milling.

[0008] Further, the molar ratio of ZrCl4, YCl3, InCl3, LiCl and Li2O is (0.1-0.2):0.5:(0.3-0.5):(1.2-1.5):(0.2-0.4).

[0009] In the prior art, Zr is generally used in combination with metal Li to prepare solid electrolyte materials. However, the present invention finds that by selecting Zr, Y, and In to be combined with metal Li and adjusting the ratio of O and Cl elements, the capacity retention rate of solid-state lithium batteries at room and low temperatures can be improved. The analysis shows that Zr can form a cubic phase structure with high ionic conductivity, and Y doping can increase the cubic phase stability, thereby improving ionic conductivity; In can adjust the electronic structure and ion migration path of the material, thereby improving the conductivity at low temperatures through synergistic effects.

[0010] Furthermore, the preparation method of the solid electrolyte material includes the following steps: in an Ar-filled glove box, ZrCl4, YCl3, InCl3, LiCl and Li2O are uniformly mixed, and under vacuum conditions, the temperature is first raised to 400-420°C, kept warm for 3-4 hours, then raised to 450-480°C, kept warm for 6-8 hours, and finally raised to 530-550°C, kept warm for 2-3 hours, cooled and then ball milled to obtain a solid electrolyte material.

[0011] The present invention can improve the capacity retention rate of solid-state lithium batteries at high temperatures by means of gradient heating. Analysis shows that gradient heating can achieve better physical and chemical properties of the crystal structure, and can realize solid electrolyte materials with higher lithium ion conductivity. By forming a thermally stable crystal structure, side reactions and lithium dendrite growth at high temperatures can be suppressed, thereby significantly improving the capacity retention rate of solid-state lithium batteries under high temperature conditions.

[0012] Furthermore, the rotation speed of the ball mill is 1200-1300 rpm, and the time of the ball mill is 4-6 hours.

[0013] The present invention also provides a solid-state lithium battery prepared using the solid electrolyte material.

[0014] Furthermore, the preparation method of the solid-state lithium battery comprises the following steps: (1) Grinding the solid electrolyte material, lithium cobalt oxide and acetylene black to less than 40 mesh, adding polytetrafluoroethylene binder, mixing evenly, and preparing a positive electrode film; (2) placing the solid electrolyte material in a polyetheretherketone mold and pressing it to obtain a solid electrolyte; (3) The positive electrode film is placed on one side of the solid electrolyte and pressed, and then the lithium foil is placed on the other side of the solid electrolyte and pressed to obtain an all-solid-state lithium battery.

[0015] Furthermore, the weight ratio of the solid electrolyte material, lithium cobalt oxide, acetylene black and polytetrafluoroethylene binder is 15: (30-40): (1-1.3): (0.4-0.6).

[0016] Furthermore, the pressing conditions in step (2) are 520-530 MPa and the pressing time is 4-10 min.

[0017] Further, the cathode film is placed on one side of the solid electrolyte and pressed at a pressure of 510-520 MPa for 8-15 minutes.

[0018] Further, a lithium foil was placed on the other side of the solid electrolyte and pressed under a pressure of 50-55 MPa for 2-4 min.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. In the present invention, by selecting Zr, Y, In and metal Li, and adjusting the ratio of O and Cl elements, the capacity retention rate of the solid-state lithium battery at room temperature and low temperature can be improved.

[0020] 2. The present invention can improve the capacity retention rate of solid-state lithium batteries at high temperatures by means of gradient heating. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The raw materials used in the following examples of the present invention are all commercially available products: Polytetrafluoroethylene binder, Shandong Lifan Chemical Co., Ltd.

[0023] Example 1 The present embodiment provides a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, YCl3, InCl3, LiCl and Li2O with a molar ratio of 0.13:0.5:0.37:1.4:0.3 are uniformly mixed; under vacuum conditions, the temperature is first raised to 410°C, kept warm for 3.5 hours, then raised to 460°C, kept warm for 7 hours, and finally raised to 540°C, kept warm for 2.5 hours, cooled and ball milled at a ball milling speed of 1250 rpm for 5 hours to obtain a solid electrolyte material.

[0024] A solid-state lithium battery prepared using the above solid electrolyte material, wherein the preparation method of the solid-state lithium battery comprises the following steps: (1) Grind 300 mg of solid electrolyte material, 720 mg of lithium cobalt oxide and 25 mg of acetylene black to less than 40 mesh, add 10 mg of polytetrafluoroethylene binder, mix well, and prepare a positive electrode film; (2) 100 mg of solid electrolyte material was placed in a polyetheretherketone mold with a diameter of 10 mm and pressed at a pressure of 525 MPa for 5 min to obtain a solid electrolyte; (3) 8 mg of the positive electrode film was placed on one side of the solid electrolyte and pressed at a pressure of 518 MPa for 9 min. Then, the lithium foil was placed on the other side of the solid electrolyte and pressed at a pressure of 52 MPa for 3 min to obtain an all-solid-state lithium battery.

[0025] Example 2 The present embodiment provides a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, YCl3, InCl3, LiCl and Li2O in a molar ratio of 0.2:0.5:0.3:1.5:0.3 are uniformly mixed; under vacuum conditions, the temperature is first raised to 400°C, kept warm for 4 hours, then raised to 450°C, kept warm for 8 hours, and finally raised to 530°C, kept warm for 3 hours, ball milled after cooling, the ball milling speed is 1200 rpm, and the ball milling time is 6 hours to obtain a solid electrolyte material.

[0026] A solid-state lithium battery prepared using the above solid electrolyte material, wherein the preparation method of the solid-state lithium battery comprises the following steps: (1) Grind 300 mg of solid electrolyte material, 720 mg of lithium cobalt oxide and 25 mg of acetylene black to less than 40 mesh, add 10 mg of polytetrafluoroethylene binder, mix well, and prepare a positive electrode film; (2) 100 mg of solid electrolyte material was placed in a polyetheretherketone mold with a diameter of 10 mm and pressed at a pressure of 520 MPa for 7 min to obtain a solid electrolyte; (3) 8 mg of the positive electrode film was placed on one side of the solid electrolyte and pressed at a pressure of 510 MPa for 12 min. Then, the lithium foil was placed on the other side of the solid electrolyte and pressed at a pressure of 50 MPa for 4 min to obtain an all-solid-state lithium battery.

[0027] Comparative Example 1 The difference between this comparative example and Example 1 is: a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, LiCl and Li2O with a molar ratio of 1:1.4:0.3 are uniformly mixed, and under vacuum conditions, the temperature is first raised to 410°C, kept warm for 3.5 hours, then raised to 460°C, kept warm for 7 hours, and finally raised to 540°C, kept warm for 2.5 hours, ball milled after cooling, the ball milling speed is 1250rpm, and the ball milling time is 5 hours to obtain a solid electrolyte material.

[0028] Comparative Example 2 The difference between this comparative example and Example 1 is: a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, YCl3, LiCl and Li2O with a molar ratio of 0.5:0.5:1.4:0.3 are uniformly mixed, and under vacuum conditions, the temperature is first raised to 410°C, kept warm for 3.5 hours, then raised to 460°C, kept warm for 7 hours, and finally raised to 540°C, kept warm for 2.5 hours, ball milled after cooling, the ball milling speed is 1250rpm, and the ball milling time is 5 hours to obtain a solid electrolyte material.

[0029] Comparative Example 3 The difference between this comparative example and Example 1 is: a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, InCl3, LiCl and Li2O with a molar ratio of 0.5:0.5:1.4:0.3 are uniformly mixed, and under vacuum conditions, the temperature is first raised to 410°C, kept warm for 3.5 hours, then raised to 460°C, kept warm for 7 hours, and finally raised to 540°C, kept warm for 2.5 hours, ball milled after cooling, the ball milling speed is 1250rpm, and the ball milling time is 5 hours to obtain a solid electrolyte material.

[0030] Comparative Example 4 The difference between this comparative example and Example 1 is: a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, YCl3, InCl3, LiCl and Li2O with a molar ratio of 0.4:0.3:0.3:1.4:0.3 are uniformly mixed, and under vacuum conditions, the temperature is first raised to 410°C, kept warm for 3.5 hours, then raised to 460°C, kept warm for 7 hours, and finally raised to 540°C, kept warm for 2.5 hours, ball milled after cooling, the ball milling speed is 1250rpm, and the ball milling time is 5 hours to obtain a solid electrolyte material.

[0031] Comparative Example 5 The difference between this comparative example and Example 1 is: a solid electrolyte material, and the preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, YCl3, InCl3, LiCl and Li2O with a molar ratio of 0.13:0.5:0.37:1.4:0.3 are uniformly mixed, and the temperature is raised to 450°C under vacuum conditions, and the temperature is kept for 13 hours. After cooling, the ball milling is performed at a speed of 1250 rpm and the ball milling time is 5 hours to obtain a solid electrolyte material.

[0032] Performance Testing The solid-state lithium batteries prepared in Examples 1-2 and Comparative Examples 1-5 were sealed with a sealing film and taken out of the glove box and placed in a special testing device for constant current charge and discharge testing. The test conditions were a charge and discharge voltage range of 2.5-4.2V, a charge and discharge rate of 0.1C, and test temperatures of 25°C, -30°C and 50°C, respectively. The capacity retention rate after 100 cycles was measured.

[0033] The results are shown in Table 1.

[0034] Table 1 Performance test results 25℃ Capacity retention rate% -30℃ Capacity retention rate % 50℃ Capacity retention rate% Example 1 95.7 83.6 91.1 Example 2 94.2 80.3 90.6 Comparative Example 1 82.5 67.8 74.2 Comparative Example 2 85.4 70.1 77.7 Comparative Example 3 87.6 71.3 76.5 Comparative Example 4 89.1 76.4 80.4 Comparative Example 5 86.8 74.0 83.8 From the above performance test results, it can be seen that the solid-state lithium batteries prepared in Examples 1-2 have excellent capacity retention rates at different temperatures, all of which can reach more than 80%. In particular, the comprehensive performance of Example 1 is the most outstanding.

[0035] However, the comparative examples are significantly inferior to the embodiments in terms of corresponding performance tests because they do not adopt the necessary technical solutions. The raw material compositions used in the solid electrolyte materials in comparative examples 1-4 are different, and the capacity retention rate of the solid-state lithium battery at room temperature and low temperature is reduced. In comparative example 5, gradient heating is not used, and the capacity retention rate of the solid-state lithium battery at high temperature is reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0036] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A solid electrolyte material, characterized in that: The solid electrolyte material is prepared by mixing ZrCl4, YCl3, InCl3, LiCl and Li2O, heating and then keeping the mixture warm, and then cooling and then ball milling.

2. The solid electrolyte material according to claim 1, characterized in that The molar ratio of ZrCl4, YCl3, InCl3, LiCl and Li2O is (0.1-0.2):0.5:(0.3-0.5):(1.2-1.5):(0.2-0.4).

3. The solid electrolyte material according to claim 1, characterized in that The preparation method of the solid electrolyte material comprises the following steps: in an Ar-filled glove box, ZrCl4, YCl3, InCl3, LiCl and Li2O are uniformly mixed, and under vacuum conditions, the temperature is first raised to 400-420°C, kept warm for 3-4 hours, then raised to 450-480°C, kept warm for 6-8 hours, and finally raised to 530-550°C, kept warm for 2-3 hours, and ball-milled after cooling to obtain the solid electrolyte material.

4. The solid electrolyte material according to claim 3, characterized in that The rotation speed of the ball mill is 1200-1300 rpm, and the time of the ball mill is 4-6 hours.

5. A solid-state lithium battery prepared using the solid electrolyte material according to any one of claims 1 to 4.

6. The solid-state lithium battery according to claim 5, characterized in that: The preparation method of the solid-state lithium battery comprises the following steps: (1) Grinding the solid electrolyte material, lithium cobalt oxide and acetylene black to less than 40 mesh, adding polytetrafluoroethylene binder, mixing evenly, and preparing a positive electrode film; (2) placing the solid electrolyte material in a polyetheretherketone mold and pressing it to obtain a solid electrolyte; (3) The positive electrode film is placed on one side of the solid electrolyte and pressed, and then the lithium foil is placed on the other side of the solid electrolyte and pressed to obtain an all-solid-state lithium battery.

7. The solid-state lithium battery according to claim 6, characterized in that: In the step (1), the weight ratio of the solid electrolyte material, lithium cobalt oxide, acetylene black and polytetrafluoroethylene binder is 15: (30-40): (1-1.3): (0.4-0.6).

8. The solid-state lithium battery according to claim 6, characterized in that: The pressing conditions in step (2) are 520-530 MPa and the pressing time is 4-10 min.

9. The solid-state lithium battery according to claim 6, characterized in that: In the step (3), the positive electrode film is placed on one side of the solid electrolyte and pressed at a pressure of 510-520 MPa for 8-15 minutes.

10. The solid-state lithium battery according to claim 6, characterized in that: In the step (3), a lithium foil is placed on the other side of the solid electrolyte and a pressure of 50-55 MPa is applied for pressing for 2-4 minutes.

Citation Information

Cited By

  • Modified Li3MX6 solid electrolyte material, preparation method, application and lithium metal solid-state battery thereof

    CN120127205A